2020
DOI: 10.1038/s41598-020-75010-y
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the jumping and prey-capture abilities of ant-mimicking spiders (Salticidae, Salticinae, Myrmarachne)

Abstract: Accurate morphological ant mimicry by Myrmarachne jumping spiders confers strong protective benefits against predators. However, it has been hypothesized that the slender and constricted ant-like appearance imposes costs on the hunting ability because their jumping power to capture prey is obtained from hydraulic pressure in their bodies. This hypothesis remains to be sufficiently investigated. We compared the jumping and prey-capture abilities of seven Myrmarachne species and non-myrmecomorphic salticids coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…If a good signal compensates for a poor signal (the increased deception hypothesis [ 2 ]), or if the generation of one signal constrains another (the multitasking hypothesis [ 2 ]), the two signals will be negatively correlated. Spider locomotion depends on muscles contained within the legs, but also on hydraulic power developed by muscles in the head, and thus hydraulic power depends on head morphology [ 22 ]. Indeed, the constricted morphology of ant-mimicking spiders limits their ability to jump [ 22 ], so it would not be unreasonable to expect similar constraints on locomotion, or the inverse: ant-like locomotion constraining the evolution of mimetic morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a good signal compensates for a poor signal (the increased deception hypothesis [ 2 ]), or if the generation of one signal constrains another (the multitasking hypothesis [ 2 ]), the two signals will be negatively correlated. Spider locomotion depends on muscles contained within the legs, but also on hydraulic power developed by muscles in the head, and thus hydraulic power depends on head morphology [ 22 ]. Indeed, the constricted morphology of ant-mimicking spiders limits their ability to jump [ 22 ], so it would not be unreasonable to expect similar constraints on locomotion, or the inverse: ant-like locomotion constraining the evolution of mimetic morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Spider locomotion depends on muscles contained within the legs, but also on hydraulic power developed by muscles in the head, and thus hydraulic power depends on head morphology [ 22 ]. Indeed, the constricted morphology of ant-mimicking spiders limits their ability to jump [ 22 ], so it would not be unreasonable to expect similar constraints on locomotion, or the inverse: ant-like locomotion constraining the evolution of mimetic morphology. However, we found that accuracy of morphology and locomotion were not negatively correlated, failing to support either hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Even though spiders acquire protection by resembling ants, the defensive advantage comes with costs, such as constraints on circadian rhythm, lower fecundity due to abdominal narrowing and/or constrictions (see Cushing 2012), reduced jumping and hunting abilities (Hashimoto et al 2020), and the spider becoming a target for ant specialist predators (Nelson et al 2006a, b;. Mimicry is expected to occur only if the benefits of closely resembling the model exceed the costs.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which ant-mimicking spiders resemble ants is constrained by predation pressure and several other factors. Slender body shape and thin legs may constrain accurate mimics in their jumping and prey capturing abilities (Hashimoto et al 2020), while constricted abdomen may reduce fecundity (McIver & Stonedhal 1993). Developmental, genetic and life history parameters also impose constraints (Pekár & Jarab 2011, McClean et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have measured various traits such as body shape, size, color, movement, and walking trajectories that contribute to mimicry. (Shamble et al 2017, Hashimoto et al 2020, Pekár et al 2020. However, these studies have not compared all three players (model, mimic, and non-mimic) in the mimetic system, nor have they included multiple traits that contribute to mimicry (but see Kelly et al 2021).…”
Section: Introductionmentioning
confidence: 99%